Synthesis of Calcium Oxide from River Snail Shell as a Catalyst in Production of Biodiesel - Sasiprapha Kaewdang; Rotjapun Nirunsin (Applied Environmental Research, 2019)
This research studied synthesis of calcium oxide from river snail shells by calcination at 700, 800 and 900 °C for 4 h, and its subsequent use as a catalyst for biodiesel production. The calcium oxide fraction in calcined river snail shell was analyzed by X-ray fluorescence (XRF), X-ray diffraction (XRD) and scanning electron microscopy (SEM). The XRF result showed calcium oxide levels of 59.499 %, 70.113 % and 73.881 %, respectively, at corresponding calcination temperatures of 700, 800 and 900 °C. The SEM images revealed porous, rough, and fragile surfaces which became agglomerated at elevated temperatures. The calcium oxide obtained from each calcination temperature was utilized as a catalyst in production of biodiesel. The process used waste cooking oil and methanol in a molar ratio of 6:1, reaction temperature 60-65 ̊C for 3 h and 1-3 % by weight of catalysts. The transesterification reaction using calcined river snail shell as catalyst was compared at three temperature ranges. They results revealed that a calcination temperature of 800 ºC, a catalyst amount of 1 % resulted in maximum biodiesel yield, at 95.91 %. The properties of biodiesel, flash point, heat of combustion, acid value and methyl ester content were analyzed. The results found biodiesel from this research was qualified according to the standards of the Department of Energy Business. In conclusion, river snail shell is considered effective as a source of calcium oxide catalyst for commercial biodiesel production in the future.